Cognitive radio technology - Fette, Bruce Alan (Academic Press/Elsevier, 2009)
Few developments in the RF/wireless industry have created as much excitement as cognitive radio. The principles of this technology have even created new terms for subfields of this technology including dynamic spectrum access, white space, and spectrum sharing to name a few, and many companies now recognize that this technology will create numerous new business models, all enabled by cognitive radio principles. This book thoroughly covers current knowledge about cognitive radio (CR) concepts, principles, standards, spectrum policy issues, and product implementation details. In addition to 16 chapters that cover all the basics of cognitive radio, this new edition contains eight brand-new chapters covering cognitive radios in multiple antenna systems, policy language, the policy engine, spectrum-sensing and rendezvous techniques, spectrum-consumption models, protocols for adaptation, cognitive networking, and information on the latest standards, thus making it an indispensable resource for radio frequency and wireless engineers.